Temperature dependence of photoinduced birefringence in mixed Langmuir-Blodgett (LB) films of azobenzene-containing polymers - Silva, JR; Dall'Agnol, F. F.; Oliveira, O. N.; Giacometti, J. A. (Elsevier B.V., 2002)
The temperature dependence of photoinduced birefringence was investigated for mixed Langmuir-Blodgett (LB) films from the homopolymer poly[4'-[[2-(methacryloyloxy)ethyl]ethyl-amino]-2-chloro-4-nitroazobenzene] (HPDR13) and cadmium stearate (Cdst) and from the copolymer 4-[N-ethyl-N-(2-hydroxyethyl)]amino-2'-chloro-4'-nitroazobenzene (MMA-DR13) and CdSt. Birefringence was achieved by impinging a linearly polarized light on the LB films. The maximum birefringence achieved decreased with temperature as thermal relaxation of the chromophores was facilitated. The buildup curves for birefringence were fitted with biexponential functions representing distinctly different mechanisms with time constants. The first, fast process is thermally activated and may be represented by an Arrhenius process. The decay of birefringence after switching off the laser source was described by a Kohlraush-Williams-Watts (KWW) function, consistent with a distribution of relaxation times for the polymer system. Activation energies were obtained from Arrhenius plots of the rate constant of the exponential functions and KWW function, which showed that the buildup of birefringence was very similar for the two polymer systems. The decay, however, was slower for the LB film from MMA-DR13/CdSt. (C) 2002 Published by Elsevier B.V. Ltd.
Keywords: azobenzene polymers; Langmuir-Blodgett films; photoinduced birefringence